(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online shopping has emerged one of the most vital factors for economic growth and employment opportunities as it has transformed the conventional physical markets hence increasing the market capacity for existing or new products and service delivery. This is because the growth of the digital marketplace has enabled SMEs to extend their market to the international market and reduce the hurdles. This has in one way or the other boosted a lot of economic development in the areas of production, market outlet and convenience. Besides the enhancement of sale and revenue, e-commerce has provided numerous employment opportunities within various sectors including transport, information technology, advertisement and customer service. There has also been the need for digital skills which has also led to the creation of new posts and thus has supported the workforce. Besides, e-commerce platforms have improved the lives of the people in the following ways; by making it easier for individuals to engage in self-employment by providing cheaper means of doing businesses thus promoting the economic status of a particular society. However, there are challenges to the establishment of e-commerce for sustainable growth, which are infrastructure, regulation and digital literacy. E-commerce is important in development and growth of economies, innovation and employment thus it is a factor of economic growth in both the developing and the developed countries.